Acute Kidney Injury in Pregnant Women: Etiologies, Management Strategies, And Maternal-Fetal Outcomes in A Tertiary Care Setting - Rani KN, Druvitha; V Kamat, Amitha (Journal of Neonatal Surgery, 2025)
Background: Acute kidney injury (AKI) in pregnancy is a life-threatening complication associated with significant maternal and neonatal morbidity and mortality. Predisposing factors include hypertensive disorders (e.g., preeclampsia), hemorrhage (notably postpartum hemorrhage), and sepsis. Early diagnosis and expeditious management—including hemodynamic stabilization and renal replacement therapy—are paramount for improving outcomes. Methods: A retrospective observational study was performed at the Karnataka Institute of Medical Sciences (KIMS), Hubli, Karnataka, over six months (May 2024–November 2024). Forty-nine pregnant or postpartum women (up to six weeks post-delivery) with AKI were identified from hospital records. Data on demographics, obstetric parameters, etiology of AKI, mode of delivery, renal replacement therapy (dialysis) requirements, and maternal-fetal outcomes were analyzed. Key findings were summarized using bar charts and pie charts to illustrate distributions of age, parity, mode of delivery, etiologies, dialysis requirements (including number of cycles), maternal mortality, causes of death, and trends in serum urea/creatinine. Results: Hypertensive disorders (40.8%) were the most frequent etiology, followed by postpartum hemorrhage (30.6%) and sepsis (14.3%). Dialysis was required in 24 (49.0%) women; among these, 9 succumbed to complications (37.5% mortality in the dialysis subgroup). Overall maternal mortality was 28.6% (n=14), primarily attributed to multiorgan dysfunction syndrome, septic shock, and coagulopathy. Fetal/neonatal deaths occurred in 24.5% (n=12), often linked to extreme prematurity, low birth weight, or severe maternal compromise. Conclusion: AKI during pregnancy and the postpartum period remains a serious clinical challenge, especially in resource-constrained settings. Early detection of predisposing conditions, prompt resuscitation, and the availability of renal replacement therapy can substantially improve maternal and neonatal survival. Strengthening antenatal care, timely referral pathways, and critical care infrastructure are crucial strategies to curtail mortality and morbidity.